Reach and Range of Business Process Management - Findings in the Telecommunication and Chemical Industry - Becker, Jörg; Ortbach, Kevin; Plattfaut, Ralf; Niehaves, Björn (46th Hawaii International Conference on System Sciences, 2013)
Business Process Management (BPM) has become an established management practice. Current literature in this field identifies maintaining a process-aware IT landscape and managing boundary-crossing relations as important functions in BPM. Regarding the former, we understand BPM range as the level of process-awareness in the IT landscape. As for the latter, we view BPM reach as the potential utilization of boundary-crossing relations. Based on these two dimensions, we propose a framework for exploring development paths in BPM implementations. This framework is then exemplarily applied in two case studies in the telephone and chemical industries. We are able to identify a development towards a higher level of BPM range in both industries while only the telecommunication company is looking to increase its BPM reach. Based on our empirical findings, we derive generalizable propositions for BPM development in both dimensions for future theory building efforts.